Notions of genre - Grant, Barry Keith; Kurtz, Malisa (University of texas, 2016)
Much of the writing in film studies published today can be understood as genre criticism, broadly speaking. And even before film studies emerged as an academic discipline in the 1970s, cultural observers within and beyond the academy were writing about genre films and making fascinating attempts to understand their conventions and how they speak to, for, and about the culture that produces them. While this early writing on genre film was often unsystematic, impressionistic, journalistic, and judgmental, it nonetheless produced insights that remain relevant and valuable today.